Kvinneforeningene, institusjonsbyggingen og den nasjonale velferdspolitikken. Nord-Norge før 1940 - Hamran, Torunn (Universitetsforlaget, 2007)
Hensikten med artikkelen er å belyse lokale kvinneforeningers innsats som institusjonsbyggere, hvilke samarbeidsrelasjoner og politiske maktforhold de inngikk i, og hvilken betydning deres innsats kan ha fått for utformingen av den norske velferdsstaten. Rettighetsaspektet i form av trygder og ytelser og den partipolitiske debatten rundt dette har fått stor plass i deler av den skandinaviske velferdsforskningen, mens tjeneste- eller praksisaspektet har fått tilsvarende mindre plass. Dermed blir også kvinnenes bidrag fraværende. Det er sjelden nok å rette blikket mot emner og felt som har vært forsømt uten samtidig å utvikle analysemåter som forandrer selve blikket. Prior to 1940, at least 35 institutions had been established in Northern Norway under the aegis of voluntary associations affiliated to the three largest humanitarian organisations in Norway. This article discusses the role of these associations as institution-builders, and, more specifically, the institutions founded, owned and run by local associations of women volunteers providing non-professional care and services for the sick and convalescent in Nordland in Northern Norway. All these associations were led and run by women and became important institutions in the local communities they served. Together, they must also have had some influence on the very structure of these emerging institutions in Norway, and consequently have a place today in the more extensive discussion of the status of women in the growth and shaping of the Norwegian welfare state. One principal objection to previous research is that the growth of the welfare state was linked too closely to policy at national level – to government, to decision-making powers and to formal structures. This choice of perspective resulted in the absence of women’s organisations from empirical analysis. Criticism was countered with the claim that the conclusions reached would nevertheless have been the same; namely, that while women had scope for action locally they did not influence national ...